From Superillas to tactical greneery. ﻿Experiments and transcalar strategies of vegetal regeneration of urban space - Emanuela Coppola; Leonardo Zaffi; Michele D’Ostuni (Agathón)
New urban action, based on the development of green areas as a strategic tool for upgrading the city from an environmental, social and cultural point of view, is at its most innovative, the result of transversal initiatives at different levels by a variety of subjects. Experimentation and policies relating to the city and its neighbourhoods interact and are enriched in their relationship with local strategies and networks of punctual micro-interventions through spontaneous, bottom-up initiatives. This paper intends to highlight how today, in the varied design of the city, there is a common thread between large-scale planning experiences (municipal metropolitan plans), those on a neighbourhood scale of the Superillas, the Ville du Quart d’Heure and those on a small scale of Tactical Greenery. The common goal of creating green infrastructure for the future will be to permeate city living spaces.